Enhancing Consumer Satisfaction: The Impact of Retail Ambiance and Service Quality in the Beauty Industry: Meningkatkan Kepuasan Konsumen: Dampak Suasana Ritel dan Kualitas Layanan di Industri Kecantikan - Firdiyanti, Tasya Adelia; Purwanto, Nuri (Universitas Muhammadiyah Sidoarjo, 2023)
This study employs a quantitative, descriptive approach to investigate the influence of retail ambiance and service quality on consumer satisfaction within the beauty industry. Utilizing purposive sampling, data was collected from 100 clients of a beauty salon. Survey distribution through Google Forms and data analysis using SPSS revealed that the diverse retail ambiance and high service quality significantly contribute to consumer happiness, highlighting the importance of these factors in the beauty treatment sector. These findings underscore the need for beauty service providers to continually improve their shop environment and service quality to meet the rising demand for beauty treatments and enhance overall customer satisfaction. Highlight: This study employs a quantitative approach to assess the impact of retail ambiance and service quality on consumer satisfaction in the beauty industry. Findings demonstrate that a diverse retail ambiance and high service quality significantly contribute to consumer happiness. The study underscores the importance of continuous improvement in shop environment and service quality to meet growing demand and enhance overall customer satisfaction in the beauty treatment sector. Keyword: Consumer Satisfaction, Retail Ambiance, Service Quality, Beauty Industry, Survey Analysis